2018
DOI: 10.1007/s00213-018-4882-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the intracellular signaling “STOP” and “GO” pathways for the treatment of alcohol use disorders

Abstract: In recent years, research has identified the molecular and neural substrates underlying the transition of moderate “social” consumption of alcohol to the characteristic alcohol use disorder (AUD) phenotypes including excessive and compulsive alcohol use which we define in the review as the GO signaling pathways. In addition, growing evidence points to the existence of molecular mechanisms that keep alcohol consumption in check and that confer resilience for the development of AUD which we define herein as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 213 publications
(341 reference statements)
0
19
0
Order By: Relevance
“…Data obtained in rodents suggest that inhibition of mTORC1 in the brain dampens numerous adverse behaviors associated with alcohol use 10,17,21,24 . In contrast, inhibition of mTORC1 does not alter the consumption of natural rewarding substances 40 , suggesting that inhibition of mTORC1 does not affect reward per se . Furthermore, inhibition of mTORC1 is not aversive or rewarding, nor does it alter locomotion 40 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Data obtained in rodents suggest that inhibition of mTORC1 in the brain dampens numerous adverse behaviors associated with alcohol use 10,17,21,24 . In contrast, inhibition of mTORC1 does not alter the consumption of natural rewarding substances 40 , suggesting that inhibition of mTORC1 does not affect reward per se . Furthermore, inhibition of mTORC1 is not aversive or rewarding, nor does it alter locomotion 40 .…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, inhibition of mTORC1 does not alter the consumption of natural rewarding substances 40 , suggesting that inhibition of mTORC1 does not affect reward per se . Furthermore, inhibition of mTORC1 is not aversive or rewarding, nor does it alter locomotion 40 . Importantly, a single administration of Rapamycin or RapaLink-1 produces a long-lasting attenuation of excessive alcohol use and relapse 21,23 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Over more than a decade, we and others observed that the BDNF system interacts with alcohol in a unique way (Logrip et al, 2015;Ron and Berger, 2018). We found that moderate but not excessive intake of alcohol increases the expression of BDNF in the dorsal striatum and more specifically in the dorsolateral striatum (DLS) of rodents (Jeanblanc et al, 2009;Logrip et al, 2009;McGough et al, 2004) resulting in the activation of TrkB/ERK1/2 signaling (Jeanblanc et al, 2013;Logrip et al, 2009;McGough et al, 2004), and in the induction of the dopamine D3 receptor (Jeanblanc et al, 2006) and preprodynorphin (Logrip et al, 2008) gene expression, which in turn keeps alcohol drinking in moderation.…”
Section: Introductionmentioning
confidence: 99%
“…As disruption of normal BDNF signaling in the brain promotes the development of heavy alcohol use in rodents and possibly in humans (Ron and Berger, 2018), and as lowered serum BDNF levels are associated with AUD, we set out to determine if the same is true for the BDNF machinery in the peripheral blood serum of rats. We further determined whether the decrease in BDNF serum content is associated with alterations in the levels of microRNAs targeting BDNF.…”
Section: Introductionmentioning
confidence: 99%